2021
DOI: 10.3892/mmr.2021.12020
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124 facilitates lens epithelial cell apoptosis by inhibiting SPRY2 and MMP-2

Abstract: Age-related cataract (ARC) is the primary cause of blindness worldwide. Abnormal expression of microRNAs (miRNAs/miRs) has been reported to be associated with multiple diseases, including ARC. However, the potential role of miR-124 in ARC remains unclear. The present study used the human lens epithelial cell line, SRA01/04, to investigate the potential role of miR-124 in ARC. Reverse transcription-quantitative PCR analysis was performed to detect the expression levels of miR-124, protein sprouty homolog 2 (SPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…To validate miR-124a’s potential function as a metastasis suppressor, we transduced 113/6-4L melanoma cells with lentiviral vectors carrying mCherry-luciferase and a GFP-tagged single decoy against miR-124a (Dc-124a) or a scrambled decoy control (Dc-Scr). We confirmed that the miR-124a decoy efficiently inhibited miR-124, as miR-124a levels were reduced ( Figure 2A ), an indicator of decoy activity ( 33 ), and established targets of miR-124a EZH2 ( 34 ), MAPK14 ( 35 ), and SPRY2 ( 36 ) were significantly upregulated ( Figure 2B ). Nude mice were inoculated with Dc-124a- or Dc-Scr-transduced melanoma cells in the left heart ventricle and monitored by luminescence imaging throughout the experiment ( Figure 2C ).…”
Section: Resultssupporting
confidence: 57%
“…To validate miR-124a’s potential function as a metastasis suppressor, we transduced 113/6-4L melanoma cells with lentiviral vectors carrying mCherry-luciferase and a GFP-tagged single decoy against miR-124a (Dc-124a) or a scrambled decoy control (Dc-Scr). We confirmed that the miR-124a decoy efficiently inhibited miR-124, as miR-124a levels were reduced ( Figure 2A ), an indicator of decoy activity ( 33 ), and established targets of miR-124a EZH2 ( 34 ), MAPK14 ( 35 ), and SPRY2 ( 36 ) were significantly upregulated ( Figure 2B ). Nude mice were inoculated with Dc-124a- or Dc-Scr-transduced melanoma cells in the left heart ventricle and monitored by luminescence imaging throughout the experiment ( Figure 2C ).…”
Section: Resultssupporting
confidence: 57%
“…LINC00452 overexpression also notably abolished the effect of oxLDL on lipid accumulation (Figure 3B). It has been reported that the changes in MMP are also associated with the promotion of cell apoptosis (28). Therefore, the degree of MMP in HUVECs was determined.…”
Section: Linc Overexpression Restores Oxldl-induced Inhibition Of Huv...mentioning
confidence: 99%
“…Microarray analysis revealed several miRNA expression differences in cataract crystalline lens compared with normal lens tissue [14] . A growing body of research now indicates that the miRNA-mRNA axis regulates the activity of lens epithelial cells and is involved in the development of cataracts [13,15,16] , indicating their potential as a new candidate therapeutic target. For example, the upregulation of Let-7b microRNA has been observed in cataracts and promotes cataract progression [12] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the upregulation of Let-7b microRNA has been observed in cataracts and promotes cataract progression [12] . Furthermore, miR-221 and miR-124 were also dysregulated in cataracts, suggesting that these miRNAs may play an important role in the pathogenesis of cataracts [13,16] . Therefore, there is an urgent need to identify promising miRNAs for the non-surgical treatment of cataracts due to the vacancy of effective miRNAs for cataracts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation